Estudio de Factibilidad para la creación de un centro gerontológico de integración para el adulto mayor en la ciudad de Loja - Camacho Pardo, Carla Alexandra (2018)
In our country, thanks to the technological advances in medicine, the life expectancy of the older adult population has increased, but not in the same cadence in specialized gerontological care spaces for this group of people. The city of Loja, day by day grows, so it is necessary that there are centers of this type for people to occupy, these centers become active social beings. That is why this thesis has as a general objective: to carry out a "Feasibility Study for the Creation of a Gerontological Integration Center for the Elderly in the City of Loja", with the creation of this gerontological center it is intended to comply with a valuable support for the care of the elderly population. In this feasibility study all the factors were taken into account in order to know the viability of the creation of a gerontological center for the elderly in the city of Loja, such as: In the objectives, it was proposed to carry out the four studies that contain an investment project, so we have a market study, technical study, financial study and financial evaluation. For the fulfillment of the specific objectives it was necessary to use methods and techniques such as: inductive and deductive method. Within the information collection techniques, direct observation, the survey and the interview were used 6 in terms of information collection instruments. The main questionnaire was taken as a tool to obtain all the information that was necessary for the development of this information. thesis project. Then the discussion is presented where the four studies were developed as we have: in the market study the older adult population was established, which is 20,101 inhabitants and through the application of the surveys, the use of the service was determined with an average of 6 months and the demands such as: potential demand for the year one of 69,951 with an acceptance of 58% the actual demand for year one of 58,060 with a percentage of 83% and finally the effective demand is those customers who will use the services of the gerontological center that will be 58,060 with a percentage of acceptance of 100%. In the offer, in this feasibility study three 3 gerontological centers were seen that offer the service to the elderly, which for year one is 1,620 annual services with an increase of 3% according to data obtained from the Ministry of Health. Economic and Social Inclusion (MIES). Regarding the unsatisfied demand, 34,084 were obtained for the first year. In the technical study, fundamental aspects of the project's engineering, size, and location were determined. with regard to the organizational study, the type of society that will be implemented through organizational charts and function manuals was determined. 7 The financial study presents a budget in which the initial investment is determined, which is $ 87,518.16 dollars, which was financed 40% by the Development Bank. In the financial evaluation, through the analysis of the economic indicators it was possible to determine the viability of the project. where the following results were obtained: the NPV of the project is 114,535.92 demonstrating the feasibility of execution of the same, then the IRR is 31.18%. The Beneficial Relationship Cost is 0.44 cents for each dollar invested. It was also found that the company recovers the capital invested in 4 years, 7 months and 10 days and finally the sensitivity analysis supports an increase of 15.20% in costs and a decrease of 10.67%. Finally, the conclusions in which it is considered that the creation of the gerontological center will have a favorable acceptance allowing to develop the respective recommendations for its creation.